Gibberellic Acid Production from Corn Cob Residues via Fermentation with Aspergillus niger - Mariel Monrroy; José Renán García (Journal of Chemistry)
Following numerous biotechnological innovations, a variety of agricultural by-products can now be employed as low-cost substrates for the production of secondary metabolites, such as antibiotics, phytohormones, biofuels, pesticides, and organic acids. As an example, gibberellin (GA) growth phytohormones can be obtained by such means, wherein gibberellic acid (GA3) is of great interest worldwide in the agricultural sector. The central aspect of this research therefore focused on the bioconversion of agricultural by-products, such as corn cob, to obtain GA3 phytohormone via solid-state fermentation (SSF) with Aspergillus niger. The chemical characterization of the obtained material showed that the corn cob possessed glucose, mannose, arabinose, and lignin contents of 34, 26, 8, and 16%, respectively. Our results also indicated an appreciable carbon content (47%), in addition to the mineral elements of nitrogen (4%), potassium (1.2%), iron (0.03%), sodium (0.01%), calcium (0.06%), and Al (0.02%). Following SSF for 11 d in the presence of A. niger at pH 5, 30°C, and 24% sample consistency, a GA3 production of >6.1 g·kg−1 was obtained. This value is higher than those previously reported for different by-products of the food industry, such as coffee husk, wheat bran, cassava, pea pods, and sorghum straw (i.e., 0.25–5.5 g·kg−1) following SSF. The production of GA3 from corn cob residues not only contributes to reducing the negative impact of agricultural by-products but also represents a new source of a key raw material for phytohormone production, thereby contributing to the development of processes to convert agricultural residues into biologically active compounds of commercial interest.